BUSINESS PLANNING TRAINING PROGRAM TO DEVELOP ENTREPRENEURIAL INTERESTS OF THE YOUNGER GENERATION IN TEGALSARI VILLAGE OF TEGALSARI CITY - Habibi, Beni; Apriani, Dewi; Yulianto, A. Rony (Universitas Negeri Semarang, 2020)
A step is needed to build entrepreneurial interests of the younger generation, one of which is to create a program that accommodates the aspirations of generations to increase their business interests, namely through entrepreneurial training programs. Business planning training program for the younger generation is done in Tegalsari Village, Tegalsari. This business planning training program aims to increase entrepreneurial interest for young people and guide the business preparation process ranging from the introduction of types of businesses to the preparation of businesses through examples of businesses made by participants. Based on the results of the training activities that have been carried out, it can be drawn as follows. Participants' knowledge of entrepreneurship is very strong as seen from pre-test and post-test results. This result is quite proud because most participants are participants who have received entrepreneurial counseling in the previous year. The delivery of knowledge about the preparation of business planning can improve the knowledge and understanding of participants about the objectives and benefits and the importance of making business planning before deciding to be entrepreneurial Diperlukan sebuah langkah untuk membangun minat berwirausaha para generasi muda yaitu salah satunya dengan membuat sebuah program yang menampung aspirasi para generasi untuk meningkatkan minat usahanya yaitu melalui program pelatihan kewirausahaa. Program pelatihan perencanaan usaha untuk generasi muda ini di lakukan di kelurahan Tegalsari Kota Tegal. Program pelatihan perencanaan usaha ini bertujuan untuk meningkatkan minat wirausaha bagi kalangan muda dan membimbing proses penyusunan usaha mulai dari pengenalan jenis – jenis usaha sampai dengan menyusun usaha melalui contoh usaha yang dibuat oleh peserta. Berdasarkan hasil pelaksanaan kegiatan pelatihan yang telah dilakukan, dapat ditarik simpulan sebagai berikut. Pengetahuan peserta mengenai kewirausahaan tergolong sangat kuat yang terlihat dari hasil pre-test dan post-test. Hasil ini cukup membanggakan karena sebagian besar peserta adalah peserta yang telah mendapatkan penyuluhan kewirausahaan pada tahun sebelumnya. Penyampaian pengetahuan tentang penyusunan perencanaan usaha dapat meningkatkan pengetahuan dan pemahaman peserta mengenai tujuan dan manfaatnya serta pentingnya membuat perencanaan usaha sebelum memutuskan berwirausaha.